Role of neo-adjuvant chemotherapy followed by surgery in cervical cancer: a review - Bharaswadkar, Ganesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Incidence of cervical cancer is predominantly found in developing countries. In Indian set up, it is most commonly found in rural locations in younger population. Chemotherapy was initially introduced for the treatment of recurrent/metastatic cervix cancer and has subsequently been explored in primary treatment either as neo-adjuvant prior to radiation or surgery in an attempt to reduce the incidence of loco-regional recurrence. The review study tries to evaluate the role of neoadjuvant chemotherapy (NACT) followed by surgery in cervical cancer management. Randomized trials and meta-analysis were analysed. Most of them used short course chemotherapy course of 4-6 weeks followed by surgery. patients with high risk pathological features received postoperative RT. The results of trials indicated significant reduction in the risk of death with NACT, but there were few differences between the trials. NACT followed by surgery is found to be associated with an improved response rate and progression-free survival. However, the impact on overall survival remains to be confirmed.